(3JWhQ GdacQ hGdhbGFY GdEbJUGOjI (B/s - (3eUWai, CMeO aQjOs; (3MSf, SgjQ eMeO GdSjO s ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2000)
(3GdacQ hGdfXGe GdEbJUGOj aj eQMdI GdYUhQ GdhSWi(B- (3ePgH GdJLGQjf hXghQ GdQCSeGdjI GdJLGQjI aj GdaJQI ef (B1450-1750-(3GdQCSeGdjI GdUfGYjI hadSaI GdKhQI GdUfGYjI aj GdaJQI ef YGe (B1750-1850-(3CKQ GdfgVI GdUfGYjI hGdJjGQ GdacQ GdeYGUQ dgG Ydi GdEbJUGO(B- (3JYeb GdCReI aj GdfXGe GdQCSeGdj aj NdGd GdaJQI ef (B1920-1945- (3deMGJ aj GbJUGOfG GdeYGUQ(B- (3GdJMhdGJ GdeQMdjI ddEbJUGO GdeUQj(B- (3SjGSI GdEfaJGM GdEbJUGOj hBKGQgGs
Keywords: (3GdETJQGcjIs; (3GdEbJUGO(B- (3GdadSaIs; (3GdQCSeGdjIs; (3GdfXe GdEbJUGOjI(B- (3eUQs